2014
DOI: 10.3389/fimmu.2014.00305
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and Dynamic Expression of Activating NK Cell Receptors in the Control of Chronic Viral Infections: The Paradigm of HIV-1 and HCV

Abstract: Natural killer (NK) cell function is regulated by a balance between the triggering of activating and inhibitory receptors expressed on their surface. A relevant effort has been focused so far on the study of KIR carriage/expression setting the basis for NK cell education and self-tolerance. Focus on the evolution and regulation of activating NK receptors has lagged behind so far. Our understanding of activating receptor expression and regulation has recently improved by evidences derived from in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 114 publications
1
12
0
Order By: Relevance
“…However, the immune mechanism(s) contributing to lentivirus DNA reservoir size shaping and control still eludes our full understanding. NK cells are involved in the control of RNA and DNA viruses belonging to different virus families, including the control of retrovirus replication (11,16,32,38,61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the immune mechanism(s) contributing to lentivirus DNA reservoir size shaping and control still eludes our full understanding. NK cells are involved in the control of RNA and DNA viruses belonging to different virus families, including the control of retrovirus replication (11,16,32,38,61).…”
Section: Discussionmentioning
confidence: 99%
“…Their relevance in control of virus infections is reflected by the quantity of mechanisms that have been developed to evade NK cell activity, including skewed cytokine production (19,20), reduced NCR expression with an activated NK cell phenotype (21)(22)(23), and NCR ligand shedding or downmodulation on target cells (22,(24)(25)(26)(27). A distinct pattern of NCR expression and induction associates with a benign course of HIV infection in a minority of HIV-infected patients with low or undetectable viremia (HIV controllers [HIC], long-term nonprogressors [LTNP], and elite controllers [EC]) (28)(29)(30) and in chronically hepatitis C virus (HCV)-infected patients who respond to treatment (31,32). In addition, epidemiological DNA carriage studies showed an association between specific KIR:HLA carriage and control of HIV-1 replication (33)(34)(35).…”
mentioning
confidence: 99%
“…Some of these detect signatures of danger to induce NK cell function, while others identify characteristics of health to restrain NK cell activities. The topic of functionally diverse NK cell receptors has been reviewed extensively [7] [8] [9]. Those considered in the current study with regards to considering local healthy donor ranges are listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory receptor diversity is mostly dependent on the genetic background, whereas activating receptors appear to be more influenced by environmental factors. 7 Increased attention has been paid to the inhibitory receptor function and involvement in the process of NK-cell education to self-tolerance and anti-viral and antitumor immune response, 7,8 whereas less is known about the regulation of activating NK-cell receptors. The importance of NKcell receptors in mediating antitumor immune response is further supported by the identification of several mechanisms of immune escape, mainly consisting in the downregulation of activating receptors and their ligands, or alternatively in the upregulation of inhibitory receptor-ligand pairs.…”
Section: Introductionmentioning
confidence: 99%